1998
DOI: 10.1146/annurev.ecolsys.29.1.543
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Cycle and Bioaccumulation of Mercury

Abstract: Because it is very toxic and accumulates in organisms, particularly in fish, mercury is an important pollutant and one of the most studied. Nonetheless we still have an incomplete understanding of the factors that control the bioconcentration of mercury. Elemental mercury is efficiently transported as a gas around the globe, and even remote areas show evidence of mercury pollution originating from industrial sources such as power plants. Besides elemental mercury, the major forms of mercury in water are ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
956
3
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,386 publications
(994 citation statements)
references
References 80 publications
(88 reference statements)
17
956
3
18
Order By: Relevance
“…In particular, several studies have previously reported on the influence of particular dietary contributions on THg and Se concentrations (Bergeron et al, 2007;Loseto et al, 2008;Ramos et al, 2009a). In addition, many other studies have already reported on biomagnification of these elements throughout foodwebs, considering d 15 N as a measure of trophic positions (Atwell et al, 1998;Becker et al, 2002;Cabana and Rasmussen, 1994;Jarman et al, 1996;McIntyre and Beauchamp, 2007;Morel et al, 1998). Some of these studies even found this positive pollutante d 15 N relationship at intra-specific level (Ramos et al, 2009a).…”
Section: Unravelling the Trophodynamics Of Pollutantsmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, several studies have previously reported on the influence of particular dietary contributions on THg and Se concentrations (Bergeron et al, 2007;Loseto et al, 2008;Ramos et al, 2009a). In addition, many other studies have already reported on biomagnification of these elements throughout foodwebs, considering d 15 N as a measure of trophic positions (Atwell et al, 1998;Becker et al, 2002;Cabana and Rasmussen, 1994;Jarman et al, 1996;McIntyre and Beauchamp, 2007;Morel et al, 1998). Some of these studies even found this positive pollutante d 15 N relationship at intra-specific level (Ramos et al, 2009a).…”
Section: Unravelling the Trophodynamics Of Pollutantsmentioning
confidence: 98%
“…Since Cabana and Rasmussen (1994) questions related to biomagnification of contaminants to deleterious levels in biota, have largely been addressed by considering species' trophic positions (Becker et al, 2002;McIntyre and Beauchamp, 2007;Morel et al, 1998;Stewart et al, 2004). However, direct trophic transfer of pollutants derived from local feeding opportunities and individual feeding behaviours is also considered an important pathway for contaminant acquisition (Bearhop et al, 2000;Bergeron et al, 2007;Loseto et al, 2008;Ramos et al, 2009a), adding complexity to the study of pollutant trophodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Ancillary information on fish length, weight, sex, and age is required to provide a more statistically defensible, normalized MeHg value. Other factors, such as nutrient input, watershed land use change, fluctuations in water levels in shallow ecosystems, overfishing, changes in food chain structure, and variations in species competition, can also alter fish MeHg concentration (9,27,30). Because MeHg is the dominant form in fish, measurement of total mercury is an adequate metric.…”
Section: National Atmospheric Deposition Programmentioning
confidence: 99%
“…Aquatic microorganisms transform metallic mercury into the extremely toxic methylmercury (Morel et al 1998) which is assimilated rapidly by aquatic biota and accumulates in the food chain: the bio-accumulation factor (BAF) for piscivorous fish calculated by the US EPA (1997) is 6 800 000.…”
Section: Introductionmentioning
confidence: 99%